HEUTAGOGI SEBAGAI PENDEKATAN PELATIHAN BAGI GURU DI ERA REVOLUSI INDUSTRI 4.0 - Rohmat Sulistya (Jurnal Pendidikan dan Kebudayaan, 2019)
The role of teachers in the era of the industrial revolution 4.0 is not only as a giver of knowledge, but also as a life-long learners, learning leaders, instructors of learning resources, network former, and communication opener. These roles are inseparable from the demands of rapid change in all areas. Therefore, to adjust with the rapid changes, teachers must learn all the time throughout life. To achieve these roles, it is important to design about such updating teacher competencies’ training approaches that fit to the challenges of the 21st century. This study aims (1) to reveal the challenges of the industrial revolution 4.0 for teachers; and (2) offers the heutagogical approach to teacher training along with the outline its implementation steps. The study was carried out by analysing literatures comprehensively, referring to books, journals, and conference articles to answer the objectives of the study. The results of the study revealed that: (1) teachers faced major challenges to present interesting learning that fit with the conditions of millennial students and the challenge of responding to learning issues related to behavior, methods, and learning processes; (2) training programs with heutagogical approach need to be considered because it is a self-determined learning and and its implementation steps is by strengthening HOTS (Higher Order Thinking Skills) learning, strengthening digital literacy, developing a complete and reliable learning management system platform, and implementing teacher training with a heutagogy approach. To conlude, it is hoped that heutagogy can be an alternative approach of teachers training to produce teachers who are prepared for industrial revolution 4.0 learning challenges.